Tanggung Jawab Notaris terhadap Penyimpanan Minuta Akta sebagai Bagian dari Protokol Notaris - Cut Era Fitriyeni (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: A notary is a public officer which has an authority to issue authentic document and other authorities as ruled in Article 15 of the Notary Act. In regard with original legal documents made and witnessed by notary, a notary has an obligation to keep it as ruled by Article 16 (1) words b and i of the Act. However, the Act doesnot regulate how the procedure and the way of keeping it hence it is prone to damage, loss and destruction.  The Responsibility of Notary Towards Keeping the Minutes of Legal Document as a Part of Notary Protocol